MAPK-activated protein kinase 2 is associated with poor prognosis of glioma patients and immune inhibition in glioma - Sun, Jinmin; Wu, Sicheng; Zhao, Wenyu; Xue, Senrui; Zhang, Lei; Ren, Jing (Frontiers in Oncology, 2024)
Introduction An effective therapeutic method to noticeably improve the prognosis of glioma patients has not been developed thus far. MAPK-activated protein kinase 2 (MAPKAPK2) is a serine/threonine kinase, which is involved in tumorigenesis, tumor growth, metastasis, and the inflammatory process. The clinical significance and molecular function of MAPKAPK2 in glioma remain unclear. Methods MAPKAPK2 expression in human glioma tissues was detected by immunohistochemistry and analyzed from the transcriptome sequencing data in TCGA and CGGA. Prognostic nomogram was constructed to predict the survival risk of individual patients. GO and KEGG enrichment analyses were performed to analyze the function and pathways MAPKAPK2 involved. Single-cell RNA sequencing data was used to analyze the cell types in which MAPKAPK2 was enriched. Flow cytometry was used for cell cycle and apoptosis detection. The ability of cell proliferation and migration was analyzed by CCK8 and cell migration assay, respectively. Correlation analyses were performed to analyze the relationship of MAPKAPK2 with immune infiltration, immune regulators, chemokine, and chemokine receptors. Results MAPKAPK2 was not only aberrantly upregulated in glioma tissues but also correlated with poor clinical characteristics. Moreover, MAPKAPK2 was prevalent in isocitrate dehydrogenase (IDH) wild-type and 1p/19q non-codeletion glioma cohorts and predicted poor prognosis of glioma patients. MAPKAPK2 may be involved in cell proliferation, cell migration, DNA damage repair, and immune regulation in glioma. MAPKAPK2 was enriched in microglia/macrophages and malignant tumor cells. Further investigation into cellular function revealed that inhibiting MAPKAPK2 suppressed the proliferation and migration of glioblastoma multiforme (GBM) cells in vitro. The inhibition of MAPKAPK2 significantly induced the G1 cell cycle arrest and cell apoptosis of GBM cells. Consistent with the enriched function of MAPKAPK2 in immune regulation, MAPKAPK2 was correlated with immune cell infiltration in glioma tissues. Mechanistically, a series of immune regulators, immunomodulatory chemokine, and chemokine receptors were positively correlated with MAPKAPK2 expression. Discussion Our findings provide evidence of the clinical relevance of MAPKAPK2 in prognosis evaluation of glioma patients and highlight the underlying significance of MAPKAPK2 in glioma therapy.